Unicidade para equações dos tipos: Burgers, Kuramoto-Sivashinsky e Schrödinger - Cuayla Zapata, Miguel Angel (2017)
Based on Carleman's estimates and under certain conditions of linear exponential decay we prove uniqueness for equations of type: Burgers, Kuramoto-Sivashinsky and Schrödinger.